The Effect of Compensating Balance Requirements on the Profitability of Borrowers and Lenders - Kolodny, Richard; Seeley, Peter; Polakoff, Murray E. (Journal of Financial and Quantitative Analysis, 1977)
Richard Kolodny, Peter Seeley, Murray E. Polakoff, The Effect of Compensating Balance Requirements on the Profitability of Borrowers and Lenders, The Journal of Financial and Quantitative Analysis, Vol. 12, No. 5 (Dec., 1977), pp. 801-815